CRITICAL VALUE OF GLUCOSE USING CRITIVA 1.0 APPLICATION IN BALI MANDARA EYE HOSPITAL - Pande Putu Ayu Patria Dewi; Dewa Putu Yudhi Ardhiana; I Dewa Putu Gede Wiyata Putra (JURNAL WIDYA MEDIKA, 2023)
Critical value is very critical result in laboratory examination that can indication several emergency conditions. Reporting critical values are controversial between hospital management, clinicians, and laboratory. Reporting critical value required effective communication. Information technology has become one of the solution effective communication in reporting critical values. Critical values can occur in clinical chemistry, hematology, and other laboratory examination. Glucose is one of the clinical chemistry parameters which is often foound critical value and therapy must be given immediately. Aim of this research is to evaluated time reporting using Critiva 1.0 application in cellular phone of clinical pathologist Bali Mandara Eye Hospital. Samples were 50 times reporting the glucose critical value simulation using the Critiva 1.0 application and 50 times reporting the Standard Operating Operations (SPO) simulation at the Bali Mandara Eye Hospital. Simulation carried by laboratory techonology in charge. We used means to analyze time reporting and SPSS version 16. Mean reporting glucose critical value using Critiva 1.0 application was 12 seconds. Mean reporting glucose critical value using SPO Bali Mandara Eye Hospital was 720 seconds.